2007
DOI: 10.1007/bf03324681
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and survival of rural and urban seniors: results from the Canadian Study of Health and Aging

Abstract: Frailty index analysis readily summarizes health and mortality differences between very old rural and urban dwellers, which reflect differences in deficit accumulation, and in the impact of gender on survival. The frailty index provides efficient dimensionality reduction for studying group differences in the health of older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 34 publications
4
42
0
1
Order By: Relevance
“…Curcio et al (2014) suggested multiple factors identified to be associated with frailty, including increasing in age, lower education, presence of chronic diseases, poor self-reported health status, low dependence in basic and instrumental activities of daily living, depression and cognitive impairment. Further, a study done in Canada comparing the prevalence of frailty in urban and rural areas reported differences, with the rural had a higher prevalence than urban area (Song et al 2007). It seems that this sample from sub-urban of Malaysian was more likely to be pre-frail probably due to diseases and unhealthy lifestyle.…”
Section: Discussionmentioning
confidence: 79%
“…Curcio et al (2014) suggested multiple factors identified to be associated with frailty, including increasing in age, lower education, presence of chronic diseases, poor self-reported health status, low dependence in basic and instrumental activities of daily living, depression and cognitive impairment. Further, a study done in Canada comparing the prevalence of frailty in urban and rural areas reported differences, with the rural had a higher prevalence than urban area (Song et al 2007). It seems that this sample from sub-urban of Malaysian was more likely to be pre-frail probably due to diseases and unhealthy lifestyle.…”
Section: Discussionmentioning
confidence: 79%
“…[16][17][18][19][20] The prevalence of frailty using a frailty index approach has been less well studied, although age-associated distributions of deficit accumulation have been multiply replicated. [21][22][23][24][25][26][27][28] Here, the objectives were to estimate the prevalence and 10-year outcomes of frailty using a deficit accumulation approach in a representative survey of community-dwelling older adults in Canada. The frailty prevalence estimations that used other definitions of frailty will also be discussed, to follow the increasing call for comparative studies 2,12,29,30 when conducting frailty research.…”
mentioning
confidence: 99%
“…Many papers validated and compared the characteristics of the FI in comparison to the phenotype frailty and clinical frailty [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%